2012
DOI: 10.1061/(asce)mt.1943-5533.0000514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Seismic Responses of Geosynthetically Reinforced Walls with Tire-Derived Aggregates and Granular Backfills

Abstract: This paper reports the seismic responses of geosynthetically reinforced walls with two types of backfills using shake table tests. The backfills are tire-derived aggregates (TDA) and poorly graded sand, respectively. Mechanically stabilized earth (MSE) walls with reinforced TDA backfill have not been fully tested under seismic conditions. In this study, two geosynthetically reinforced walls are tested on a one-dimensional shake table. A section of reduced-scale MSE wall (1.6 m high, 1.5 m deep, and 1.5 m long)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…The seismic performance of retaining walls constructed with TDA has been evaluated in large-scale experiments recently by Xiao et al (2012) and Ahn and Cheng (2014), who found that TDA has a softer response than natural granular soils and advantageous seismic characteristics such as lower dynamic earth pressures and the ability to experience large residual deformations without catastrophic failure. However, these studies did not report TDA cyclic shear properties that are needed to simulate seismic performance, such as variation of shear modulus and damping ratio with cyclic strain magnitude under different stress conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seismic performance of retaining walls constructed with TDA has been evaluated in large-scale experiments recently by Xiao et al (2012) and Ahn and Cheng (2014), who found that TDA has a softer response than natural granular soils and advantageous seismic characteristics such as lower dynamic earth pressures and the ability to experience large residual deformations without catastrophic failure. However, these studies did not report TDA cyclic shear properties that are needed to simulate seismic performance, such as variation of shear modulus and damping ratio with cyclic strain magnitude under different stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the resilient modulus is not as useful as the shear modulus versus cyclic shear strain relationship, studies on resilient modulus may provide further insight into the cyclic response of TDA. Bosscher et al (1997) Two recent studies have evaluated the seismic response of TDA used as a backfill in gravity retaining walls (Ahn and Cheng 2014) and geosynthetic-reinforced retaining walls (Xiao et al 2012). Ahn and Cheng (2014) performed a shake table test on a large-scale (2 m high) cantilever 6 retaining structure constructed from a layer of Type B TDA and an overlying layer of sand, and found that the dynamic pressure exerted on the wall was smaller in the TDA layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Roh [23] proved that the dynamic earth pressures behind a retaining wall were reduced on using a backfill material having lesser elastic modulus and higher damping ratio and demonstrated that tire chips possesses these reliable properties. Xiao et al [24] conducted reduced scale model tests on retaining walls of height 1.6 m backfilled with tire derived aggregate (TDA) under static and seismic loading conditions and compared the results with that of conventional sand as backfill. It has been found that the displacements of the wall, accelerations in the backfill soil, static and dynamic stresses in the backfill were reduced by using TDA due to the lesser unit weights and higher damping ratios of rubber materials.…”
Section: Introductionmentioning
confidence: 99%
“…When TDA is used in embankments and retaining walls, it may be used in tandem with geosynthetic reinforcements to form mechanically-stabilized TDA (MS-TDA) walls (Xiao et al 2012). The pullout interaction between geogrids and tire chips as well as soil-tire chip mixtures is an important topic related to MS-TDA walls that has been studied by several researchers (Bernal et al 1996(Bernal et al , 1997Tatlisoz et al 1998;Tanchaisawat et al 2010).…”
Section: Introductionmentioning
confidence: 99%